Utility and limitations of cardiac tissue slices for the study of cardiac electrophysiology - Wang, K (2015)
Cardiac tissue slices, a rarely used pseudo two-dimensional preparation, have gained increasing popularity for applications such as drug testing over the last ten years as they combine ease of handling with patho-physiologically relevant cell-type representation, distribution and inter-connection. The most well-established methods to measure electrophysiology in cardiac tissue are sharp electrodes and multi-electrode-arrays, techniques which are limited in spatial resolution or signal content. In this work, we have applied dual voltage Ca2+ optical mapping on cardiac slices, allowing us to record these two key parameters simultaneously at high spatio-temporal resolution, yielding better visualisation of conduction waves, spatial dispersion in action potential (AP) characteristics, and intracellular Ca2+ transient (CaT). The slice preparation method and the measurement protocols were refined to yield good reproducibility. Data analysis routines were developed to extract relevant parameters reliably. Despite being a promising candidate for drug testing, little is known about how slice and intact whole-heart AP properties are interrelated, and how to scale-up from observations in two dimensions (2D) to the three dimensional (3D) heart. In this thesis, we present a method to compare directly AP properties of intact whole-heart and tissue slices, and show the extent to which slices preserve AP characteristics. We have explored the suitability of tissue slices as an experimental model to study stretch induced changes in AP and CaT. During axial stretch, a dynamic profile of both AP and CaT was observed with an initial shortening of both AP and CaT duration, followed by a gradual recovery/prolongation. We have also used tissue slices to study spatial heterogeneity of AP and CaT properties in the rabbit left ventricular free wall. A transmural gradient can be captured in CaT and AP (with the longest APD and CaT durations being captured in the subendocardium). No large AP prolongation was found in the mid-myocardium. We conclude that the cardiac tissue slice preparation preserves some key functional parameters of the whole heart and is a promising model to study cardiac electrophysiology.